Reading habits among students of SK Tanjong Apong, Samarahan / Dayang Hanida Abang Usop - Abang Usop, Dayang Hanida (2015)
Reading habit should start from young itself. A good reading habit is an essential among school children in order to create a good reading culture. The purposes of this study are to identify the reading habits and attitudes among Primary 4, 5 and 6 or commonly called Level 2 students in SK Tanjong Apong, Samarahan towards reading English materials; study the relationship between their reading habits and the reading attitudes and; compare reading habits and reading attitudes with their Mid Semester I test scores. A pre-tested questionnaire was used for collecting data and 66 students participated in this study. The findings of this study suggest that majority of the participating students showed positive habits and attitudes towards reading English materials. They were also motivated to read for academically related reasons such as, to obtain better results in examinations; improving their language skills and for learning new things as well. Reading was the fourth most favourable activity out of 14 activities after watching television, drawing and doing outdoor activities. It was also found that a huge number of the students were Marginal, Forced and Reluctant Readers based on analysis done on their frequency of reading outside school hours, library visit duration of time spent on reading daily and their Mid Semester 1 test scores in English subject. This study offers few recommendations for promoting good reading habits among students in SK Tanjong Apong and all students as well.